Easy crafts for the insane a mostly funny memoir of mental illness and making things - Brown, Kelly Williams (New York : G.P. Putnam's Sons, 2021)
"From the New York Times bestselling author of Adulting comes a story about how to make something when you're capable of nothing"--
Within a two-year period Brown's marriage collapsed, she broke three limbs in unrelated incidents, her father was diagnosed with cancer, and she fell into a deep depression. One of the few things that kept her moving forward was crafting. Simple, rustic creations were the joy and accomplishments she found in her worst days. No matter how disconnected Brown felt, she could still fold a tiny paper star, and that's not nothing. In showing how crafting tutorials served as the backdrop of a life dissolved, she provides a poignant and hysterical look at the unexpected, messy coping mechanisms we use to find ourselves again.
Introduction. Thank, or at least acknowledge, your lucky stars -- Unmarried : in which I leave my spouse; flee to Independence, Oregon; and assume a future so bright, protective eyewear is required -- Ascendant : in which I establish a new family, join tinder, and fall in love over the course of one evening -- Dislocated : in which Trump becomes president, my bones crumble to dust, and we all become 25 to 33 percent crazier -- No apparent distress : in which I break my other arm and meditate on the nature of independence in a time of growing darkness -- Scenes from a breakdown : in which I just cannot get a win -- A fertile time : in which I seek the meaning of family and find some truly terrible ideas -- My almost-dying : in which I do the worst thing -- Psych ward crafting : in which I lose all my freedoms but gain some new makeup skills -- Well ... ish : in which I gain a lot of sanity and lose a lot of mobility -- So it's time to reconstitute your whole dang life : in which I do that exact thing -- Afterword : ... And now, here we all are.
111169
Keywords: Brown, Kelly Williams; Brown, Kelly Williams -- Mental health; Depressed persons -- United States -- Biography; Women authors, American -- Biography; Handicraft -- Therapeutic use; Depression in women -- Humor; Handicraft -- Humor; Biography & Autobiography / Personal Memoirs; Crafts & Hobbies / General; Self-Hel[p / Mood Disorders / General; Autobiography; Wit and Humor